2019
DOI: 10.4103/ijo.ijo_1729_18
|View full text |Cite
|
Sign up to set email alerts
|

Repeat keratoplasty in failed Descemet stripping automated endothelial keratoplasty

Abstract: Purpose:To evaluate the clinical factors associated with repeat Descemet stripping automated endothelial keratoplasty (DSAEK) or penetrating keratoplasty (PKP) in cases of failed DSAEK.Methods:Retrospective observational study of cases with failed DSAEK admitted to our center for a repeat keratoplasty over 5 years (January 2013–Decemeber 2017) was undertaken. Demographic and perioperative details of all cases and type of repeat keratoplasty were recorded. Logistic regression analysis was performed to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An Indian study that enrolled a large sample of patients reported that glaucoma was the primary factor in eyes that underwent repeat DSAEK. [ 25 ] A long-term review of graft failure 20 years after PK also noted late endothelial decompensation as the main reason for poor results in PBK. [ 26 ] Pl remove this sentence Thus, the issue of GTE requires attention to increase success with keratoplasty for managing PBK.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study that enrolled a large sample of patients reported that glaucoma was the primary factor in eyes that underwent repeat DSAEK. [ 25 ] A long-term review of graft failure 20 years after PK also noted late endothelial decompensation as the main reason for poor results in PBK. [ 26 ] Pl remove this sentence Thus, the issue of GTE requires attention to increase success with keratoplasty for managing PBK.…”
Section: Discussionmentioning
confidence: 99%
“…A repeat graft is one of the most frequent indications of keratoplasty, and a re-graft may be required in 5% to 10.5% of cases after EK. [ 11 12 ] A defective posterior capsule increases the incidence of intraoperative complications during a repeat keratoplasty, including vitreous prolapse, IOL dislocation, and extrusion which adversely impacts graft survival. In addition, a loss of posterior capsule integrity will lead to difficulties in ensuring adequate air tamponade in anterior chamber during a repeat surgery, with high likelihood of migration of air posteriorly and subsequent graft dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies (n = 403 eyes) analyzed the outcomes of repeat DSEK (re-DSEK). [61][62][63][64][65][66][67][68][69][70] The 2 main indications for re-DSEK were failed primary DSEK graft and poor visual performance after primary DSEK. Prior aqueous shunt surgery, donor graft CEC density, and at least 1 documented postoperative rejection episode were the main factors associated with the need for DSEK graft exchange after primary DSEK in a multivariable model.…”
Section: Repeat Dsekmentioning
confidence: 99%
“…63 Reported visual outcomes seem to be similar to those achieved for primary DSEK surgery, 67 with mean CDVA after re-DSEK ranging from 0.50 to 0.18 logMAR (Snellen equivalent 20/30-20/63). 63,64,66,70 Besides, maximal postoperative CDVA after re-DSEK reported rates of eyes reaching CDVA ≥20/40 following re-DSEK ranges from 20% to 100%. [62][63][64] If studies with ≤2 eyes were excluded from this analysis, then the proportion of eyes reaching CDVA ≥20/40 would be 20%-82%, and no studies observed eyes reaching CDVA ≥20/25.…”
Section: Repeat Dsekmentioning
confidence: 99%
See 1 more Smart Citation